Effect of acupuncture on the opening time of implantation window and endometrial receptivity in controlled ovarian hyperstimulation rats during peri-implantation period - Hu, Runan; Huang, Yanjing; Song, Yufan; Wu, Xiao; Song, Kunkun; Huang, Guangying; Zhang, Mingmin; Dong, Haoxu (Frontiers in Endocrinology, 2023)
Purpose: To investigate the effect of acupuncture for improving the pregnancy rate of COH rats from the viewpoint of regulating the opening time of the implantation window and endometrial receptivity. Methods: Experimental rats were randomly divided into normal group (N), model group (M) and acupuncture group(A), and samples were collected on Day 4, 5 and 6 after mating. COH rats were treated with acupuncture at SP6, LR3, and ST36 once a day for 7 times. The pinopodes were observed under a scanning electron microscope. Serum estrogen and progesterone levels were measured via ELISA. The protein and mRNA levels of estrogen receptor (ER), progesterone receptor (PR), leukemia inhibitory factor (LIF), integrin β3, vascular endothelial growth factor (VEGF), and fibroblast growth factor 2 (FGF-2) in the endometrium were evaluated via West-blot, immunohistochemistry, and PCR. Results: Compared with group N, the pregnancy rate of group M was significantly decreased (P<0.05), and the abnormal serum hormone levels and implantation window advancement were observed. Compared with group M, the pregnancy rate of group A was significantly increased (P<0.05), the supraphysiological serum progesterone levels were restored to normalcy (P<0.05), and the advanced implantation window was restored to a certain extent. Further, the abnormal ER, PR, LIF, integrin β3, VEGF, and FGF-2 expression levels of the endometrium got recovered to varying degrees. Conclusion: Acupuncture may restore the estrogen and progesterone balance in COH rats and the forward shift of the implantation window to a certain extent, improving the endometrial receptivity and finally improving the pregnancy rate of COH rats.